2016
DOI: 10.1093/ejcts/ezw164
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral mammary artery grafting increases postoperative mediastinitis without survival benefit in obese patients

Abstract: In obese patients, CABG surgery using BIMA instead of SIMA increased the risk of postoperative DSWI, without improving survival. According to our results, short-term postoperative risks of infection associated with BIMA are not offset by longer-term benefits in that patient population. Special care should be exerted when selecting conduits for myocardial revascularization in obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 24 publications
2
23
0
3
Order By: Relevance
“…The use of chlorhexidine was instructed to be performed for 5 days before surgery since chlorhexidine has the theoretical advantage of longer antimicrobial activity (>48 hours), compared with 2 hours of isopropyl alcohol alone . The prevalence of mediastinitis before implementation of the CCPPM was 1.4%, which is similar to the general incidence previously described in the literature . After the implementation of the CCPPM occurred an expressive reduction of mediastinitis to 0.09% (virtually null).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The use of chlorhexidine was instructed to be performed for 5 days before surgery since chlorhexidine has the theoretical advantage of longer antimicrobial activity (>48 hours), compared with 2 hours of isopropyl alcohol alone . The prevalence of mediastinitis before implementation of the CCPPM was 1.4%, which is similar to the general incidence previously described in the literature . After the implementation of the CCPPM occurred an expressive reduction of mediastinitis to 0.09% (virtually null).…”
Section: Discussionsupporting
confidence: 64%
“…13 The prevalence of mediastinitis before implementation of the CCPPM was 1.4%, which is similar to the general incidence previously described in the literature. 14,15 After the implementation of the CCPPM occurred an expressive reduction of mediastinitis to 0.09% (virtually null). The findings of the post-CCPPM period cannot be attributed to the higher prevalence of comorbidities 16…”
Section: Discussionmentioning
confidence: 98%
“…In a similar retrospective study by Ruka and colleagues, 5583 obese patients were included. After propensity score matching, BITA was not associated with significantly improved long-term survival at a median follow-up of 7.4 years [42]. In a large trial of 1,526,360 patients, obesity was identified as an independent risk factor for SWI, but in the BITA group, only patients with chronic complications of diabetes had a significantly higher risk with an OR of 1.90 (95% CI 1.51-2.41) [18].…”
Section: Bita Grafting In Obese Patientsmentioning
confidence: 83%
“…In the Benedetto cohort, the frequency of deep sternal wound infection (DSWI) was 2.6% in the BITA group and 0.9% in the SITA group, but the difference did not reach statistical significance [41]. In the Ruka study, the frequency of DSWI was 3.2% in the BITA group, and 1.1 in the SITA group (P < 0.001) after matching [42].…”
Section: Bita Grafting In Obese Patientsmentioning
confidence: 99%
“…However, based on the Society of Thoracic Surgeons National Database report, less than 4% of patients undergoing CABG receive BIMA grafts . The reason for reluctance to use BIMA grafts may be that there is still concern about an increased risk of sternal wound infection using BIMA, particularly in patients with diabetes mellitus, and/or obesity . We believe that avoiding sternotomy by performing robotic BH‐TECAB in obese patients is the most effective way to avoid this risk altogether while allowing the benefits of using BIMA grafts.…”
Section: Resultsmentioning
confidence: 99%